Association between the number of chronic pain sites and neuropathic-like symptoms in community-dwelling older adults with chronic pain: a cross-sectional study. Issue 2 (8th February 2023) - Saito, Takafumi; Chen, Tao; Yatsugi, Harukaze; Chu, Tianshu; Liu, Xin; Kishimoto, Hiro
Abstract : Objectives: We investigated the relationship between the number of chronic pain sites and the prevalence and severity of neuropathic-like symptoms in community-dwelling older Japanese adults with chronic pain. Design: Cross-sectional study. Setting: The data analysed are from a study conducted in the city of Itoshima, Japan in 2017. Participants: The study population was 988 participants (age 65–75 years) not in need of long-term care who completed questionnaires assessing sociodemographic factors, psychological factors and chronic pain. Primary outcome measures: The primary outcome was the participants' neuropathic-like symptoms evaluated by the PainDETECT Questionnaire (PD-Q). We classified the participants into mild and moderate-to-severe pain groups according to the pain intensity on the PD-Q. The number of chronic pain sites was categorised into groups with 1, 2–3 and ≥4 sites. Results: The age-adjusted and sex-adjusted prevalence of neuropathic-like symptoms was significantly higher among the participants with 2–3 or ≥4 sites compared with the single-site group. In the binomial logistic regression analyses, the multivariable-adjusted ORs and 95% CIs for neuropathic-like symptoms among the participants with 2–3 and ≥4 sites were 1.94 (1.13 to 3.33) and 3.90 (2.22 to 6.85), respectively compared with the participants with single-site pain. The ORs for moderate-to-severe neuropathic-like symptoms increased significantly with the increase in the number of chronic pain sites. Conclusions: The number of chronic pain sites was positively associated with the presence and severity of neuropathic-like symptoms in community-dwelling older Japanese adults with chronic pain.